EDUKASI KOMUNIKASI KELUARGA TERKAIT PENANGANAN “SIBLING RIVALRY” MELALUI NEW MEDIA TIKTOK - Khoridatun Nafi'ah; Mutia Rahmi Pratiwi (Universitas Tidar, 2022)
Abstract: TikTok’s social media not only offers entertainment but becomes one of the modern family education media. Family education content is needed, but not many provided it is “sibling” related content. The existence of Rensia Sanvira’s TikTok account which provides “sibling” family communication education is an opportunity for parents to gain knowledge in it. The purpose of this study is to identify educational content on Rensia Sanvira’s TikTok account based on the nurturing aspect so that an ideal “sibling” family communication picture can ben known. This research uses a qualitative approach with content analysis methods. The results showed that the educational content on Rensia Sanvira’s TikTok account provided theoretical and practical family communication education, and prioritizes justice for every child. Keywords: TikTok, Educational Media, Sibling Abstrak: Media sosial TikTok tidak hanya menawarkan hiburan namun menjadi salah satu media edukasi keluarga kekinian. Konten edukasi keluarga yang sangat dibutuhkan, namun tidak banyak yang menyediakannya adalah konten terkait “sibling”. Adanya akun TikTok Rensia Sanvira yang memberikan edukasi komunikasi keluarga “sibling” menjadi kesempatan orang tua untuk mendapatkan pengetahuan didalamnya. Tujuan penelitian ini adalah untuk mengidentifikasi konten edukasi pada akun TikTok Rensia Sanvira berdasarkan aspek nurturing sehingga dapat diketahui gambaran komunikasi keluarga “sibling” yang ideal. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis isi. Hasil penelitian menunjukkan bahwa konten edukasi pada akun TikTok Rensia Sanvira memberikan edukasi komunikasi keluarga “sibling” secara teoritis dan praktek, serta mengedepankan keadilan pada masing-masing anak. Kata kunci: TikTok, Media Edukasi, Sibling